1957
DOI: 10.1182/blood.v12.5.409.409
|View full text |Cite
|
Sign up to set email alerts
|

Erythrokinetics. IV. The Plasma Iron Turnover as a Measure of Erythropoiesis

Abstract: Experimental and clinical studies have been performed to define more clearly the significance of the plasma iron turnover. It has been shown that the plasma iron turnover is not affected by the rate of red cell destruction and to only a limited extent by increased body stores. It does, however, reflect the degree of erythroid marrow activity and is a sensitive indicator for measuring changes in such activity. A series of 85 studies in normal subjects and in patients with various h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

1958
1958
1967
1967

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(20 citation statements)
references
References 0 publications
2
17
0
1
Order By: Relevance
“…One last point relates to the significance of the siderosis which was a major feature in the Bantu subjects studied. This association, which has also been observed by other workers (Schulz and Swanepoel, 1962) seemed to be more than fortuitous since the degrees of iron overload present were greater than would be expected in a hospital population of comparable age structure (Bothwell and Isaacson, 1962). It has been suggested that persons with siderosis living on a borderline diet may be precipitated into clinical scurvy as a result of irreversible oxidation of available ascorbic acid by the excessive deposits of ferric iron.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…One last point relates to the significance of the siderosis which was a major feature in the Bantu subjects studied. This association, which has also been observed by other workers (Schulz and Swanepoel, 1962) seemed to be more than fortuitous since the degrees of iron overload present were greater than would be expected in a hospital population of comparable age structure (Bothwell and Isaacson, 1962). It has been suggested that persons with siderosis living on a borderline diet may be precipitated into clinical scurvy as a result of irreversible oxidation of available ascorbic acid by the excessive deposits of ferric iron.…”
Section: Discussionsupporting
confidence: 72%
“…Although the present investigation was designed primarily to study iron metabolism in scurvy, the results obtained give some insight into the pathogenesis of anaemia in this condition. In the subjects studied, erythroid marrow activity was in the range which would be expected as a result of acute anaemia (Bothwell et al, 1957) and both in-vivo and in-vitro studies suggested that haemoglobin formation was normal. The anaemia present in these subjects must therefore have been the result of a degree of haemolysis and/or haemorrhage greater than the marrow's capacity to respond.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations